FABRIKASI SEL SURYA DENGAN MENGGUNAKAN BUAH SENDUDUK (MELASTOMA MALABATHRICUM) SEBAGAI SENSITIZER DAN PEMBUATAN NANOMATERIAL TIO2 MENGGUNAKAN TEKNIK SOL-GEL - Ngaderman, Hubertus; S, Ego Srivajawaty; Fitri, Yulia (Sistem Informasi, 2017)
[Computation and modeling] The current solar cell technology is a technology developed by a process that is cheaper and easier in manufacturing. The solar cells sensitized by a dye below abbreviated writing that the DSSC is often also called GrÃ¤tzel cells or whether the writing in Indonesian to be Sel Surya Berbasis Pewarna Tersensitisasi (SSPT). DSSC is a potential candidate in as a third generation of solar cells (coming soon) because it does not require a material with a high degree of purity so that a low-cost production process. Dye used as a sensitizer can be either synthetic or natural. Metal-based organic dye complex ruthenium using synthetic (it is expensive), but it contains heavy metals that harm the environment. To reduce the cost of DSSC develops organic based on material sensitizer. DSSC using the same principles for the process of photosynthesis that behave as a chlorophyll dye that absorbs light and produces carrier.The effectiveness of DSSC is no doubt that reaching more than 10% but with using this expensive type which is ruthenium complex metal-based organic. It is necessary to study massive research, a material awareness survey that has good performance, environmental costs. In this study will be carried out using DSSC senduduk fruit dye (Melastoma malabathricum) manufacturing and oxide semiconductors are nano materials (nanocrystals) TiO2 anatase gradually the solvotermal techniques.